Enhancing China's Competitiveness Through Lifelong Learning - Dahlman, Carl; Zhihua Zeng, Douglas; Wang, Shuilin (Washington, DC: World Bank, 2012)
This study emphasizes that in response to demands for wider access and better quality of education, and to achieve economies of scale and leverage limited resources, China needs to develop a more integrated system of education and training with appropriate bridges and interfaces among its various constituents. This book outlines the key elements of such a system, focusing primarily on its economic aspects. It presents a framework to help identify and understand the demands being placed on the education and training system and the services that various education providers can supply, highlighting several policy approaches to building an effective and efficient lifelong learning system. These include changing the role of government from being the main provider of education and training to being the architect, facilitator, and rule-keeper for a more inclusive system. In this scenario, government would ensure quality, relevance, efficiency, and equity through sound accreditation, assessment, and vocational qualification systems, stronger linkages with the labor market, partnerships with nongovernmental players, and better resource allocation and financial aid programs. It would also provide information services for all stake-holders, develop an education finance market, tap into private resources to meet the increasing demand for education and training, and harness the potential of distance education.